Methods for the analysis of dynamic structures of telecommunication systems - Волотка, Вадим Сергеевич; Поповский, Владимир Владимирович (Eastern-European Journal of Enterprise Technologies, 2013)
Mathematical models of connectivity of the system associated with the network structures for their reliability are considered. For static systems in where the connection matrix consists of the probability characteristics, the rate of the connection is defined as a stochastic estimation. For complex systems, the calculation of this index has the NP-complexity. Therefore, the evaluation of connectivity is calculated from the approximate methods. Such techniques such as assessment Ezary-Proschan and Polesski and others are known. For dynamic systems the connected component is of fundamental importance because it is the mutual coupling between elements of the system ensure the acquisition highly-integrated properties of emergence. As a model of a dynamic system the equation of state of a shaping filter or basic differential model Chebotarev-Agaev is considered. Besides, the latter is adequately reduced to an equation of stochastic approximation, a simplified version of which is used in telecommunication technologies to assess the round-trip time RTT, RED algorithms and others. Evaluation of the status and results of the analysis for the different connections between the elements are presented.